One man's Bible a novel - Gao, Xingjian 1940- (HarperCollins publishers, 2002)
A fictionalized account of the author's life under Mao Zedong and the Cultural Revolution describes how the political climate of Beijing rendered his home one of perpetual fear for its citizens.
Keywords: Gao, Xingjian -- Fiction; Political fiction; Geschichte; China -- History -- Cultural Revolution, 1966-1976 -- Fiction; Autobiografie; Fiktionale Darstellung; Autobiographical fiction